Effect of knowledge sharing and technological innovation capabilities on competitive advantage on MSME’s culinary sector - Musa, Chalid Imran; Sahabuddin, Romansyah; Tawe, Amiruddin; Haeruddin, M. Ikhwan Maulana (The Economics and Finance Letters, 2023)
This research aims to examine and analyze the results of knowledge sharing and technological innovation capabilities on competitive advantage. This research’s focus is on the MSMEs in the culinary industry in Makassar city. The approach to sampling in this study was a purposive sampling method, whereas the data collection technique used was a questionnaire. The examination of the data was conducted using path analysis. Results show that knowledge sharing has an impact on technological innovation capabilities, knowledge sharing has an effect on competitive advantage, technological innovation capabilities have an effect on competitive advantage, and knowledge sharing has an effect on competitive advantage through technological innovation capabilities. In terms of their relation to technological innovation capabilities, MSMEs in the culinary sector in the city of Makassar have their own challenges in managing their businesses. Companies have limitations in implementing the use of technology, especially MSMEs that are micro in nature and are still pioneering. Based on the results and discussion, it can be concluded that 1) knowledge sharing has an effect on technological innovation capabilities in culinary sector MSMEs in Makassar city; 2) knowledge sharing has an effect on competitive advantage in culinary sector MSMEs in Makassar city; 3) technological innovation capabilities shape the competitive advantage in the culinary sector MSMEs in the city of Makassar; and 4) knowledge sharing has an effect on competitive advantage through technological innovation capabilities in the culinary sector Makassar city’s MSMEs, which shows that the higher the knowledge sharing, the higher the competitive advantage through technological innovation capabilities.